Exploring the effects of time-restricted eating on body weight and associated cardiometabolic outcomes in South African women living with HIV (TESSA): protocol for a randomised controlled trial - Andre P Kengne; Julia H Goedecke; Jonas Salling Quist; Ole F Olesen; Kristine Færch; Dirk L Christensen; Amy E Mendham; Lorena Heckens; Fatima Hoosen; Majken Lillholm Pico; Joel Dave; Louise Groth Grunnet (BMJ Open)
Introduction We codesigned an intervention with a low-resourced community with the aim to investigate the effects of time-restricted eating (TRE) on changes in body weight and associated cardiometabolic outcomes in South African women living with overweight/obesity and HIV who have initiated dolutegravir (DTG)-based antiretroviral therapy (ART).Methods and analysis Women with overweight or obesity (body mass index ≥25 kg/m², no upper limit), aged 20–45 years, living with HIV and in a low-resourced community, and receiving DTG-based ART for less than 2 years will be recruited from a community healthcare centre in Khayelitsha, Cape Town (n=152). Participants will be randomised 1:1 to the TRE group (n=76) or standard of care control group (n=76) for 12 months. The TRE group will be required to restrict their eating window to ~8–10 hours/day and will receive nutritional information sessions at baseline and at 3, 6, 9 and 12 months. The primary outcome of body weight will be assessed at baseline and monthly. Cardiometabolic measures will be reported as secondary outcomes. At baseline, 6- and 12 months, an oral glucose tolerance test (to estimate insulin sensitivity and beta-cell function), questionnaires (sociodemographic, food insecurity, quality of life, social support and sleep quality) and a quantified food frequency questionnaire (total energy and macronutrient composition) will be completed. Every 3 months, appetite ratings, bioelectrical impedance (fat mass and fat-free mass), fasting venous bloods (glucose, insulin, gut hormones and systemic inflammation) and process evaluation (qualitative interviews) will be completed. Monthly monitoring will also include anthropometry and blood pressure.Ethics and dissemination The study is conducted in accordance with the Declaration of Helsinki and has been approved by the Human Research Ethics Committee of the University of Cape Town (628/2021). Verbal and written consent is required from study participants. Results of this study will be published in peer-reviewed journals and presented at conferences.Trial registration number PACTR202302484999720.